(untitled) (e-Journal of Linguistics, 2020)
This research deals with compound words used in Seventy-Seven Thousand Service-Trees by Sri Chinmoy. The case is many people did not recognize and aware of using it. This research is trying to describe the types and the structure of compound words and supported by two theories, those are Booij (2007) and McCarthy (2002). In achieving the objectives, the researcher uses descriptive qualitative as the type of the research. The data are in the form of compound words. In collecting the data the writer applies documentation technique and the steps are reading attentively, selecting, collecting, and classifying the data systematically by following the types and the structure of compound words. The results of this research show that there are three kinds of compound words. From 390 the data of compound words, there are 348 data are classified as a compound noun, 20 data are classified as a compound adjective, and 22 data are classified as a compound verb. In this research, it is found that only two ways in the spelling of compound words are solid and hyphenated. There are three sub-classes of compound words found in this study those are endocentric compound, exocentric compound, and copulative compound.